PENGARUH CITRA PERUSAHAAN, KUALITAS PRODUK DAN CITA RASA TERHADAP KEPUASAN PELANGGAN - Yunita Rahmah Sari (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2021)
This study is entitled The Influence of Company Image, Product Quality and Taste on Customer Satisfaction in Bengkulu City Syarah Bakery consumers. The problem formulation in this study is whether the company's image, product quality, and taste influence the customer satisfaction of Syarah Bakery. The purpose of this study is to find out the company's image, product quality, and taste influences the customer satisfaction of Syarah Bakery. This research was conducted on Bengkulu City Bakery Syarah Consumers. While the time of this research was carried out in December 2020 until January 2021. There is also a population and this research is Syarah Bakery Kota Bengkulu, while the sample of this study is a consumer Syarah Bakery Kota Bengkulu amounting to 110 people. This means that the sample material uses quantitative methods.With the research test data analysis technique, the research results can be concluded that the respondents' responses about Company Image (X1), Product Quality (X2), and Taste (X3) affect Customer Satisfaction (Y) with multiple linear regression results obtained as follows: Y = 0.414 + 0.280 (X1) + 0.202 (X2) + 0.109 (X3). In addition, from the hypotheses that have been done, it is found that the Company Image variable (X1) shows that t_hit> t_ (α / 2) (3,945> 1.98260) and (sig α = 0.000 <0.050), Product Quality is t_hit> t_ ( α / 2) (4,517> 1.98260) and (sig α = 0.028 <0.050), Taste is t_hit> t_ (α / 2) (2,167> 1.98260) and (sig α = 0.032 <0.050). Then the test result F shows that the values of F_count> F_table are (73,505> 2,699) and (sig α = 0.000 <0.050). So it can be concluded that all variables namely Company Image, Product Quality, and Taste are partially and simultaneously compliant with Bengkulu City Bakery Lecture Customer Satisfaction.Keywords: Company Image, Product Quality, Taste and Customer Satisfaction